2023
DOI: 10.3390/jcm12227073
|View full text |Cite
|
Sign up to set email alerts
|

The Association between the Platelet to White Blood Cell Ratio and Chronic Kidney Disease in an Aging Population: A Four-Year Follow-Up Study

Yang Xiong,
Qian Zhong,
Yangchang Zhang
et al.

Abstract: Introduction: The platelet to white blood cell ratio (PWR) has been reported to be a prognostic factor for some diseases, such as subarachnoid hemorrhage. However, the association between the PWR and chronic kidney disease (CKD) remains unknown. To investigate the cross-sectional and longitudinal association between the PWR and CKD, this study was performed. Methods: This study used datasets from a national prospective cohort in China (China Health and Retirement Longitudinal Study). A retrospective cohort fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 44 publications
(59 reference statements)
0
0
0
Order By: Relevance
“…Consistent with our research findings, multiple studies have reported associations between PWR and prognosis in various malignancies and inflammatory conditions (25). Elevated PWR is significantly negatively correlated with overall survival rates among patients experiencing acute-on-chronic liver failure (34).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with our research findings, multiple studies have reported associations between PWR and prognosis in various malignancies and inflammatory conditions (25). Elevated PWR is significantly negatively correlated with overall survival rates among patients experiencing acute-on-chronic liver failure (34).…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, poor glycemic control may lead to liver damage (52), as the liver is a crucial organ for producing thrombopoietin, a platelet-stimulating factor, which could further contribute to decreased platelet count (53). Indeed, for individuals with normal blood glucose levels, an elevated PWR might correlate with improved platelet function, which is vital for preserving vascular health, hemostatic function, and immune system functionality (25). The effect of platelet and WBC counts can be simultaneously assessed by the PWR (54).…”
Section: A B Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, poor glycemic control may lead to liver damage (52), as the liver is a crucial organ for producing thrombopoietin, a platelet-stimulating factor, which could further contribute to decreased platelet count (53). Indeed, for individuals with normal blood glucose levels, an elevated PWR might correlate with improved platelet function, which is vital for preserving vascular health, hemostatic function, and immune system functionality (25). The effect of platelet and WBC counts can be simultaneously assessed by the PWR (54).…”
Section: A B Cmentioning
confidence: 99%